AN ANALYSIS OF NATURALNESS IN IDIOMATIC EXPRESSIONS OF TRANSLATION IN A NOVEL ENTITLED WANDERLUST BY DANIELLE STEEL - Rini, - (2009)
This paper entitled An Analysis of Naturalness in Idiomatic expressions of Translation in a Novel Entitled "Wanderlust" by Danielle Steel. The present paper was intended to find out the translation strategies used by the translator in accomplishing naturalness level of the translation of idiomatic expressions, to find out the naturalness from the aspect of idiomatic expressions in the novel, and to find out the problems in the translation of idioms. The data were collected from the novel both English and Indonesian versions, these consisted of 174 idiomatic expressions and their translations. This paper was conducted by using qualitative method that applied several steps. First of all, all of the idiomatic expressions found in the novel were clustered and categorized into the types of idiom by Hockett (1958). After that, the writer analyzed the data in terms of the translation strategies proposed by Baker (1992) which were applied to every type of the idiomatic expressions. Then, in analyzing the naturalness, the writer classified them into natural, less natural and unnatural. Finally, the writer analyzed the problems in the translation of idiomatic expressions in the novel. The result of the study indicated that there were six types of idioms applied in the novel. Those were 174 idiomatic expressions, namely figures of speech (65.51%), English Phrasal Compound (14.37%), Slang (13.21%), Proper Names (4.60%), Abbreviation (1.14%) and Substitute (1.14%). The translation strategies applied in translating idiomatic expressions were paraphrase (86.20%), similar meaning but dissimilar form (8.62%), similar meaning and form (2.87%) and omission (2.29%). Paraphrase was the most frequent translation strategy that was employed in the novel. The translation itself was considered natural because it achieved fine level of naturalness and the findings proved that the numbers of natural scale achieved 68.96% which meant that the text was easier to understand and had high predictability. The most problem that arouse in the translation of idiomatic expressions was that the translator tended to be inconsistent. In addition, the differences between culture of SL and TL hindered the translator from finding the right equivalence in the TL.